2019
DOI: 10.3390/dj7030080
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Two New Glass Fiber Post Systems Cemented with Self-Adhesive Resin Cements

Abstract: The aim of this in vitro study was to evaluate the adhesion strength of two new fiber post systems (FiberSite™ Post and Cytec™ Blanco Post) cemented with two different adhesive resin cements (Panavia™ SA and Maxcem™ Elite). Root canals of sixty extracted human mandibular premolars were prepared using ProTaper Universal™ rotary files (Dentsply Sirona Endodontics, York, PA, USA). The root canals were irrigated with 5.25% sodium hypochlorite (NaOCl) during instrumentation. After root canal preparation, the canals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Studies using self-adhesives as luting material for glass fiber posts showed similar results in all three root regions (cervical, middle, and apical). [ 30 31 32 33 ] However, this differs from the findings obtained in the present study, since a significantly higher bond strength was obtained in the apical region when the post surface was pretreated with 37% phosphoric acid and 1.23% APF, coinciding with the reports of Vildósola et al [ 34 ] and Boing et al [ 35 ] It is possible that the bond strength was better in the apical region because of root anatomy, since the glass fiber posts used in this study were conical in shape, making them better adapted to this region. In addition, the self-adhesive cement used (RelyX U200) showed, in other studies, better volume and fluidity at the apical region of root,[ 1 36 ] which favors good bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using self-adhesives as luting material for glass fiber posts showed similar results in all three root regions (cervical, middle, and apical). [ 30 31 32 33 ] However, this differs from the findings obtained in the present study, since a significantly higher bond strength was obtained in the apical region when the post surface was pretreated with 37% phosphoric acid and 1.23% APF, coinciding with the reports of Vildósola et al [ 34 ] and Boing et al [ 35 ] It is possible that the bond strength was better in the apical region because of root anatomy, since the glass fiber posts used in this study were conical in shape, making them better adapted to this region. In addition, the self-adhesive cement used (RelyX U200) showed, in other studies, better volume and fluidity at the apical region of root,[ 1 36 ] which favors good bonding.…”
Section: Discussionmentioning
confidence: 99%
“…A escolha do tipo de restauração de um dente tratado endodonticamente é guiada pela resistência e estética e pode exigir a colocação de pinos intrarradiculares para auxiliar na retenção das restaurações (Memon et al;Palepwad & Kulkarni, 2020), logo o propósito primário de um retentor intrarradicular é reter e estabilizar a restauração coronária que apresenta extensa perda de estrutura (Goracci;Ferrari, 2011;Aleisa et al, 2012;Freitas et al, 2019;Özlek et. al., 2019), diminuindo assim os riscos de fraturas radiculares (Gonçalves et al, 2006;Wu et al, 2007;Freitas et al, 2019;Özlek et. al, 2019).…”
Section: Introductionunclassified
“…Specifically, a lower polymerization degree can be found at the bottom of the cavity due to the decrease of light cure intensity [ 11 ]. Lately, self-adhesive resin cement characterized by a dual-cure mechanism and no dentin pre-treatment requirement has been introduced on the dental market [ 12 ]. The presence of two residual marginal ridges significantly improves long term success of post-endodontic restorations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%